Indocyanine green fluorescence angiography for bowel anastomosis assessment in ovarian cancer surgery - Gill, Stephanie J.; Yates, Elise M.; Braun, Christian; Fischer, Kyra; Santia, Maria Clara; Gelissen, Julia H.; Bartl, Thomas; Montesinos-Albert, Manel; Marchetti, Matteo; Ramirez, Pedro T. (International journal of gynecological cancer, 2025)
Optimizing bowel anastomotic integrity is a key consideration in ovarian cancer cytoreductive surgery, as anastomotic complications can significantly impact postoperative recovery and delay systemic treatment. Conventional assessment techniques like visual inspection and palpation are inherently subjective and may not consistently predict the likelihood of anastomotic leakage. Due to the serious consequences of anastomotic failure and the impact of diverting ostomies, there is growing interest in fluorescence-based technologies to enhance the diagnostic accuracy of anastomoses and support more informed intraoperative decision-making. Indocyanine green fluorescence angiography (ICG-FA) has emerged as a promising tool for improving the accuracy of bowel perfusion at the time of surgery. While widely adopted in general surgery, its use in gynecologic oncology is still growing and has not yet been established as the standard of care. By allowing surgeons to assess perfusion intraoperatively, ICG-FA may help reduce anastomotic leaks and decrease the need for diverting ostomies, with the goal of improving patient outcomes and quality of life. While early evidence indicates that ICG-FA is a safe and feasible tool in ovarian cancer surgery, additional research is required to develop standardized protocols and evaluate its clinical significance and long-term benefits. This review provides a technical overview, examines the current evidence surrounding ICG-FA in gynecologic oncology, explores its potential advantages and limitations, and highlights future directions for research in fluorescence-guided bowel anastomosis assessment.